The new economics of national defense - Clark, John J. (New York : Random House Inc., 1966)
The methodology and postulates of economic thought, consequently, have already shaped the trend of military expenditures in many important ways. Reciprocally, the experience of dealing with problems formerly considered outside the orbit of professional interest has enriched the literature of economic theory. This book is a survey of the results, a new economics of national defense, which has won for the economist a respected voice I'm deciding the great issues of war and defense.
Includes bibliographical references.
ne 17/05/2018
Loans
Keywords: War; Disarmament